Survey on Data Mining Technique - Kaur, Harmeet; Kaur, Jasleen (International Journal of Computer Sciences and Engineering, 2025)
Now a Day, Many Companies and organizations are to make a large volume of information. In the enterprise, choice producers access from all sources and types of collection methods. The information warehouse is used for the enterprise for enhancing the selection-making. In aggressive commercial enterprise international, the values of strategic statistics techniques along with these are actually identified. The enterprise surroundings, the pace isn't the simplest key to competitiveness. To investigate the records, it needs the unique equipment are called facts mining things. This paper survey of the facts mining set of rules which include Clustering, Time series, Logistic Regression, Naïve Bayes and its programs within the exclusive areas.